Myocardial Glucose Clearance by Aspalathin Treatment in Young, Mature, and Obese Insulin-Resistant Rats - Smit, Sybrand Engelbrecht; Johnson, Rabia; Van Vuuren, Mignon Alberta; Huisamen, Barbara (Planta Medica, 2018)
Rooibos, an indigenous South African plant ingested as herbal tea, is well known for its antioxidant effects. This in vitro study investigated aspalathin (C21H24O11), a dihydrochalcone unique to rooibos, for hypoglycemic effects in the context of age- and obesity-induced insulin resistance and the mechanisms involved. Male Wistar rats were allocated into three groups: 16 – 30 weeks feeding with either standard rat chow or a high-caloric diet, or 6 – 10 weeks feeding with standard rat chow. Ventricular cardiomyocytes were isolated by collagenase perfusion digestion, and glucose uptake was determined by 2-[3H]-deoxyglucose accumulation. Viability was tested by trypan blue exclusion or propidium iodide staining. The high-caloric diet significantly increased body weight gain (508.5 ± 50.0 vs. 417.3 ± 40.0 g), visceral adiposity (42.30 ± 10.1 vs. 21.75 ± 7.0 g), and fasting blood glucose (5.7 ± 0.4 vs. 4.7 ± 0.1 mM). Aspalathin (10 µM for 90 min) induced 2-[3H]-deoxyglucose uptake in young cardiomyocytes (37.2 ± 13.9 vs. 25.7 ± 2.5 pmol 2-[3H]-deoxyglucose/mg protein) and enhanced insulin-mediated 2-[3H]-deoxyglucose uptake in control cells (32.4 ± 6.4 vs. 23.5 ± 10.0 pmol 2-[3H]-deoxyglucose/mg protein), but failed to induce 2-[3H]-deoxyglucose uptake in high-caloric diet cells. Aspalathin induced glucose uptake in insulin-sensitive cardiomyocytes from young and aged rats, but not in high-caloric diet animals and enhanced the actions of insulin through a PI3K-dependent mechanism, resulting in an additive response.
Keywords: aspalathin; rooibos; obesity; insulin resistance; hyperglycemia; cardiomyocytes